Trichinellosis as an ecological problem in the Republic of Croatia - Florijančić, Tihomir; Rimac, Damir; Antunović, Boris (Acta Agraria Kaposváriensis, 2002)
Trichinellosis is considered to be a dangerous invasive zoonosis that has become the most serious public health threatening problem within invasive diseases in the last decade. The most frequent source of invasion for people is consuming of insufficiently boiled or baked and non-properly dried pork containing Trichinella spp. Monitoring of epidemiological and epizootiological situation in Croatia has shown the biggest prevalence of the disease in the areas of east Slavonija, which are marked as endemic regions. East Slavonija is well known for its traditional way of breeding and slaughtering swine, as well as for its specific processing of meet products. This way of keeping swine enables contacts with silvatic reservoirs of trichinellosis and, on the other side, gives possibility of invading wild animals by eating carrions from trichinellotic domestic swine. Rats and other sinantropic rodents, as well as non-caring out the systematic dératisation and inappropriate removing of pork with Trichinella spp. are of big importance in spreading and conveying this disease. Our primary aim in this paper was to point out the problems concerning this disease from ecological view, especially in cases when the regulations about its eradication have been carried out, as well as to provide statistical analysis of its prevalence in the endemic areas of east Slavonija.